Potential health concerns due to elevated nitrate concentrations in groundwater of villages of Vadodara and Chhota Udaipur districts of Gujarat, India. (18th November 2021) - Patel, Smruti V.; Khatri, Nitasha; Chavda, Paresh; Jha, Ashutosh K.
Abstract: In an attempt to assess the groundwater quality of Vadodara and Chhota Udaipur districts and check its suitability for drinking purposes, a total of 162 samples (50 samples during pre-monsoon season and 54 samples during post-monsoon season from Vadodara district and 29 samples during both pre- and post-monsoon seasons from Chhota Udaipur district) were collected from 63 villages of both the districts for pre-monsoon and post-monsoon seasons during 2016–17. The analysis was carried out for physicochemical characteristics and the analytical results have been interpreted by graphical representation, correlation and regression analysis and water quality index so that the quality of groundwater can be easily understood. The analytical results were then compared with the Indian Standards Drinking Water-Specification (Second Revision). From this study, it is concluded that the overall groundwater quality of the region is comparatively good; however, elevated nitrate levels resulted in many of the samples having raised concern and the necessity to make all possible efforts to improve the quality of groundwater wherever deteriorated. HIGHLIGHTS: Elevated nitrate and fluoride concentration observed in the samples collected has raised concern about the quality of groundwater. Physico-chemical analysis of groundwater quality of samples collected were compared with Indian Drinking Water Quality Standard. Correlation and regression as well as water quality index was used to determine overall quality of water. Graphical Abstract